Does the single tuition fee affect students' academic performance? Evidence from Indonesia - Arina Hasbana; Evayani Fadhilah (Journal of Educational Management and Instruction, 2024)
The rise in tuition fees has become a prominent issue in Indonesian education, especially as of 2024. It is still a concern whether the increase in UKT has a relationship with student achievement. This study aimed to determine the differences in student academic achievement based on the single tuition fee (UKT) category and the impact of UKT on student academic achievement. The sample in the study comprised 3643 samples of data on single tuition fees and student cumulative grade point averages from 2021 to 2023. Employing one sample test, ANOVA test, and linear regression analysis, the results showed that students across all UKT categories, from UKT 1 to UKT 6, surpassed the quality target standard GPA of 3.60 at UIN Raden Mas Said Surakarta. Second, the average GPA varied significantly across each category, indicating differing academic achievements among the UKT categories. Third, the UKT categories ranked from the highest to lowest score value are UKT Category 6, UKT Category 2, UKT Category 3, UKT Category 1, UKT Category 4, and UKT Category 5. Fourth, the study reveals that UKT does not impact the academic performance of students at UIN Raden Mas Said Surakarta, suggesting that other external factors not included in the study variables influence student academic achievement. Thus, increasing or decreasing UKT does not affect students’ academic achievement; instead, other external factors play a significant role in this.